Optical Properties of Sm3+ ions in Borate Glass - Ngoc, Tran; Tuyen, Vu Phi; Do, Phan Van (VNU Journal of Science: Mathematics - Physics; Vol 30 No 1, 2014)
Abstract: Samarium doped B 2 O 3 -Na 2 O-Li 2 O (BNaLi) [u1]  glasses with concentration of 0.5 mol% were prepared by the conventional melting procedure. Optical absorption, excitation, luminescence spectra and lifetime have been measured at room temperature. Judd – Ofelt (JO) theory is used to study the spectral properties and to calculate the radiative transition probabilities. The predicted [u2]   branching ratios ( β R ), radiative lifetime ( ι R ) and stimulated emission cross-sections [u3]  ( σ (λ p )) of the 4 G 5/2 excited level are reported. Keywords: Borate glass, J-O theory.   [u1] (BNaLi) borate   [u2] predicted   [u3] cross-sections